Repatriation of knowledge about insects and types through the DORSA virtual museum (Digital Orthoptera Specimen Access). - Lampe, Karl Heinz; Riede, Klaus; Ingrisch, Sigfrid (Contributions to Entomology = Beiträge zur Entomologie, 2005)
DORSA (Digital Orthoptera Specimen Access) is a virtual museum joining information on Orthoptera types and voucher specimens scattered over the major German museum collections in a single database. Data for about 16,000 specimen records including types and vouchers in over 4,000 species are searchable online via the SYSTAX database (www.biologie.uni-ulm.de/systax) which is linked to both the GBIF (Global Biodiversity Information Facility)- and BIOCASE (Biological Collection Access Service for Europe)- portals. Roughly 8,000 type specimens (with about 2,300 primary types) are documented with over 30,000 images. 12,000 sound files are also available as are geographical information and maps of the specimens in the database. DORSA specimen information is reciprocally linked to the Orthoptera Species File (OSF) which forms the taxonomic backbone for all taxon names used by DORSA. All DORSA data are freely available on the world-wide web. In this way, the knowledge about type specimens collected since colonial times is repatriated to the countries of origin.KeywordsOrthoptera, DORSA, SYSTAX, OSF, specimen database, type information, virtual museum, repatriation of knowledge.